Am80‐GCSF synergizes myeloid expansion and differentiation to generate functional neutrophils that reduce neutropenia‐associated infection and mortality. Issue 11 (13th October 2016) - Li, Lin; Qi, Xiaotian; Sun, Weili; Abdel‐Azim, Hisham; Lou, Siyue; Zhu, Hong; Prasadarao, Nemani V; Zhou, Alice; Shimada, Hiroyuki; Shudo, Koichi; Kim, Yong‐Mi; Khazal, Sajad; et al.
Abstract: Neutrophils generated by granulocyte colony‐stimulating factor (GCSF) are functionally immature and, consequently, cannot effectively reduce infection and infection‐related mortality in cancer chemotherapy‐induced neutropenia (CCIN). Am80, a retinoic acid (RA) agonist that enhances granulocytic differentiation by selectively activating transcription factor RA receptor alpha (RARα), alternatively promotes RA‐target gene expression. We found that in normal and malignant primary human hematopoietic specimens, Am80‐GCSF combination coordinated proliferation with differentiation to develop complement receptor‐3 (CR3)‐dependent neutrophil innate immunity, through altering transcription of RA‐target genes RAR β 2, C/EBP ε, CD66, CD11b, and CD18 . This led to generation of functional neutrophils capable of fighting infection, whereas neutralizing neutrophil innate immunity with anti‐CD18 antibody abolished neutrophil bactericidal activities induced by Am80‐GCSF. Further, Am80‐GCSF synergy was evaluated using six different dose‐schedule‐infection mouse CCIN models. The data demonstrated that during "emergency" granulopoiesis in CCIN mice undergoing transient systemic intravenous bacterial infection, Am80 effect on differentiating granulocytic precursors synergized with GCSF‐dependent myeloid expansion, resulting in large amounts of functional neutrophils that reduced infection. Importantly, extensive survival tests covering a full cycle of mouse CCIN with perpetual systemic intravenous bacterial infection proved that without causing myeloid overexpansion, Am80‐GCSF generated sufficient numbers of functional neutrophils that significantly reduced infection‐related mortality in CCIN mice. These findings reveal a differential mechanism for generating functional neutrophils to reduce CCIN‐associated infection and mortality, providing a rationale for future therapeutic approaches. Synopsis: Cancer chemotherapy‐induced neutropenia (CCIN) remains challenging with substantial infection‐related morbidity and mortality. Am80‐GCSF combination induces sufficient numbers of functional neutrophils to reduce CCIN‐associated infection and mortality, suggesting a novel approach for CCIN treatment. Am80‐GCSF generates large amounts of functional neutrophils without causing myeloid overexpansion. Neutrophils generated by Am80‐GCSF in CCIN mice undergoing continuous systemic intravenous bacterial infection significantly reduce infection‐related mortality of CCIN mice. Am80‐GCSF modulates the activity of the transcription factor RARα to alter expression of RA‐target genes that regulate granulocytic differentiation and development of neutrophil innate immunity. Abstract : Cancer chemotherapy‐induced neutropenia (CCIN) remains challenging with substantial infection‐related morbidity and mortality. Am80‐GCSF combination induces sufficient numbers of functional neutrophils to reduce CCIN‐associated infection and mortality, suggesting a novel approach for CCIN treatment.